Space use patterns of mountain hare () on the Alps - Bisi, Francesco; Nodari, Mosé; dos Santos Oliveira, Nuno Miguel; Masseroni, Elisa; Preatoni, Damiano G.; Wauters, Lucas A.; Tosi, Guido; Martinoli, Adriano (European Journal of Wildlife Research, 2010)
International audience Populations on the limits of species' distribution can show different behavioral adaptations to strong ecological pressure than in the central part of the range. We investigated space use patterns of alpine mountain hare () at two areas on the southern edge of the species' range. We monitored 34 hares between 2005 and 2008, estimating home range size, overlap, and site fidelity, and compared our results with space use in Scottish and North-European populations. Home ranges of mountain hares did not differ between two study areas with different habitat types. Subadult animals used larger ranges than adults and both age groups reduced home range size in autumn, a period that might be critical for hares due to changes in diet and/or high energy expenditure during the previous breeding season. Home ranges in these alpine populations were smaller than in Scandinavian populations but within the range of populations in different habitat types in Scotland. Seasonal home ranges overlapped considerably, but differed among the sexes: male-female overlap was higher than same sex (male-male and female-female) spatial overlap. Seasonal shifts of home ranges were small, and site fidelity remained high over the seasons, suggesting that resource distribution remained constant throughout the year and that the knowledge of an intensively frequented area is an important element of habitat quality. We concluded that habitat structure and availability of mates interact in affecting mountain hare space use in alpine habitats.